Evaluasi Kebijakan Sistem Zonasi Penerimaan Peserta Didik Baru (PPDB) Tingkat SMP Negeri di Kota Surabaya - Dwi Anggraini; M. Kendry Widiyanto; Anggraeny Puspaningtyas (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted with the aim of researching and evaluating the New Student Admission Zoning System Policy (PPDB) at the State Middle School level in the City of Surabaya. This research analysis was carried out using a qualitative descriptive approach. The research results show that the zoning system implemented is considered effective in achieving its main goal, namely equal distribution of quality education. However, other parents are disappointed because their children cannot attend public junior high schools because the distance between home and school is too far. So that the zoning system policy for Admission of New Students (PPDB) in State Middle Schools in Surabaya City in the future can be more optimal, the government will pay more attention to the problems faced by students during the registration process. The government must also see directly whether socialization is carried out immediately so that the implementation of the PPDB zoning system can be carried out optimally.